Comparison of Biochemical Markers of Muscle Damage and Inflammatory Response Between the Open Discectomy, Microsurgical Discectomy, and Microsurgical Discectomy Using Tubular Retractor - Linzer, Petr; Filip, Michal; Šámal, Filip; Kremr, Jan; Šálek, Tomáš; Gajdoš, Miroslav; Jarkovský, Jiří (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background One of the methods to compare the invasiveness of different surgical techniques objectively is to measure the levels of biochemical markers of systemic inflammatory response and muscle damage.Methods A total of 120 patients undergoing surgery for symptomatic disc herniation at L4–L5 and L5–S1 were enrolled in the study. Patients were operated on using open discectomy (OD), microsurgical discectomy (MD), or microsurgical discectomy with tubular retractor (MD-TUB). Myoglobin (MYO) and creatine kinase (CK) levels were used as indicators of muscle damage, and interleukin-6 (IL-6) and C-reactive protein (CRP) levels were used as indicators of systemic inflammatory response. Sampling and analysis of samples were performed preoperatively and on postoperative days 1, 3, and 7. Levels of postoperative low back pain and radicular pain were recorded on a 10-grade visual analog scale. Statistical evaluation was performed using the analysis of variance test.Results MYO concentrations in the MD-TUB group on postoperative day 1 were significantly lower than in the MD and OD groups. CK values on postoperative day 1 were significantly lower in microsurgical techniques (MD and MD-TUB) than in the OD group. The lowest IL-6 levels were found in the MD-TUB group, followed by the MD and OD groups. Differences in the IL-6 levels were significant between the groups on postoperative day 1. On all postoperative days that were monitored, values of CRP in the MD-TUB group were significantly lower compared with the MD and OD groups. Lower values in the MD group versus OD group were not statistically significant.Conclusion All studied techniques showed similar efficacy in reducing radicular pain. The microsurgical diskectomy using a retractor in comparison with MD and OD is friendlier toward the paraspinal muscles, but the difference is significant only for the MYO levels. The total stress inflammatory response exhibited by patients undergoing the MD-TUB technique is significantly lower compared with the MD and OD techniques.
Keywords: C-reactive protein; creatine kinase; discectomy; interleukin-6; myoglobin